2019
DOI: 10.1136/bmjopen-2019-028953
|View full text |Cite
|
Sign up to set email alerts
|

CADDIE2—evaluation of a clinical decision-support system for early detection of systemic inflammatory response syndrome in paediatric intensive care: study protocol for a diagnostic study

Abstract: IntroductionSystemic inflammatory response syndrome (SIRS) is one of the most critical indicators determining the clinical outcome of paediatric intensive care patients. Clinical decision support systems (CDSS) can be designed to support clinicians in detection and treatment. However, the use of such systems is highly discussed as they are often associated with accuracy problems and ‘alert fatigue’. We designed a CDSS for detection of paediatric SIRS and hypothesise that a high diagnostic accuracy together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The alert firing rate (n=12) 43 55 62 69 70 71 72 73 74 75 76 77 and alert acceptance rate (n=15) 27 29 43 58 61 62 69 74 78 79 80 81 82 83 84 were also common metrics used to understand alarm fatigue and acceptability. Although metrics of relevance such as sensitivity, specificity, and positive predictive value (PPV) were referenced several times 77 84 85 86 87 88 , only one study evaluated these metrics as pre-specified outcomes 49 . Tools for capturing clinician burnout, stress, or satisfaction after using a CDS tool were used in nine studies 26 44 78 80 82 89 90 91 92 .…”
Section: Resultsmentioning
confidence: 99%
“…The alert firing rate (n=12) 43 55 62 69 70 71 72 73 74 75 76 77 and alert acceptance rate (n=15) 27 29 43 58 61 62 69 74 78 79 80 81 82 83 84 were also common metrics used to understand alarm fatigue and acceptability. Although metrics of relevance such as sensitivity, specificity, and positive predictive value (PPV) were referenced several times 77 84 85 86 87 88 , only one study evaluated these metrics as pre-specified outcomes 49 . Tools for capturing clinician burnout, stress, or satisfaction after using a CDS tool were used in nine studies 26 44 78 80 82 89 90 91 92 .…”
Section: Resultsmentioning
confidence: 99%
“…The study is reported in accordance with the Standards for Reporting of Diagnostic Accuracy Studies (STARD) (see Additional file 1 : Appendix 1) [ 24 ]. The study protocol has been approved by the Ethics Committee of Hannover Medical School and published [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This diagnostic study was designed to evaluate CDSS accuracy by using the reference standard defined by two experienced clinicians on the base of IPSCC SIRS criteria ( primary aim ). The secondary aim was to compare CDSS accuracy to the accuracy of assessments of clinicians working in clinical routine to assess SIRS awareness of clinicians during challenging routine work [ 25 ]. The study took place at the PICU of Hannover Medical School.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the interactive interphase with voice controls are designed to assist the health care professional to work more efficiently with time saving and cost effective clinical dental practice. 3…”
Section: Clinical Decision Support System Cdssmentioning
confidence: 99%